A probabilistic assessment methodology for life cycle analysis of structures - Matos, José C. (2012)
The life cycle analysis (LCA) of structures is a framework that evaluates its condition and safety within the whole life through specific performance indicators. Management decisions are then taken considering this state and in a way that cost is optimized. Used indicators are strictly correlated and they are usually determined through a structural assessment procedure. However, this procedure is carried of different sources of uncertainty. This paper presents one methodology for a probabilistic assessment which considers and mitigates some of these uncertainties. This algorithm is based in both optimization and Bayesian inference techniques. It will be applied with two structures, respectively, a reinforced concrete and one composite beam. Two performance indicators will be computed considering traditional probabilistic assessment techniques and this methodology Obtained results pointed out the economic advantages of considering this methodology.